THE GERMAN IMMIGRATION LEGISLATION IN THE SECOND HALF OF THE XX-th CENTURY - B. G. Koybaev (Гуманитарные и юридические исследования)
The article examines the formation of political and legal immigration regulation in Germany. The author defines historical stages, conditions and background of formation of German immigration legislation.